ANALISIS PENGARUH KINERJA KEUANGAN, GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERTAMBANGAN DI BURSA EFEK INDONESIA - Citra Dirawati Pohan; Susi Dwimulyani (Jurnal Magister Akuntansi Trisakti, 2017)
This study examines the effect of financial performance, Good Corporate Governance and Corporate Social Responsibility on the value of the firm in mining companies in the Indonesian Stock Exchange. Basically, the concept of Good Corporate Governance and Corporate Social Responsibility is a concept that should be implemented in the company. The population used in this study is a mining company listed on the Indonesia Stock Exchange. Sample that used in this study are 15 companies with 3 (three) years observation from 2007 to 2009. Purposive sampling method was used in this research to obtain the samples. Data were analyzed using multiple regression analysis with SPSS version 22. Independent variables in this research are performance of firm that consist of Return on Asset and Debt to Equity Ratio; Good Corporate Governance that consist of size of board of commisiories, independency of committees member, and size of audit committees; and Corporate Social Responsibility. Dependent variable are the performance of firm that proxy by Price to Book Value. The results showed that Return on Asset, size of board of commisiories, and independency of committees’ member has a positive influence on the value of firm (Price to Book Value). While Debt to Equity Ratio, size of audit committees and Corporate Social Responsibility does not affect the value of the firm (Price to Book Value).